2020
DOI: 10.1097/sle.0000000000000891
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Hernia Repair in Cirrhotic Patients With Ascites: A Systemic Review of Literature

Abstract: Background: Umbilical hernia is a common abdominal complication in cirrhotic patients. The incidence of umbilical hernias can be up to 20% in the presence of ascites. However, there is no consensus regarding the optimal management of umbilical hernias in cirrhotic patients. The purpose of this study is to review the management of umbilical hernias in cirrhotic patients with ascites.Methods: A search of the available literature in English since 1980 was performed using PubMed, the Cochrane Library, and a search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Our data is consistent with literature demonstrating that emergency repair confers a high risk of peri-operative morbidity. 1,[3][4][5][6][7] In those that underwent immediate or delayed surgery, mortality was substantially lower than the non-surgically managed group (25 vs 73%). Multivariable analysis re-demonstrated that those who underwent surgery had lower risk of mortality despite…”
Section: Discussionmentioning
confidence: 94%
“…Our data is consistent with literature demonstrating that emergency repair confers a high risk of peri-operative morbidity. 1,[3][4][5][6][7] In those that underwent immediate or delayed surgery, mortality was substantially lower than the non-surgically managed group (25 vs 73%). Multivariable analysis re-demonstrated that those who underwent surgery had lower risk of mortality despite…”
Section: Discussionmentioning
confidence: 94%
“…Recent advances in the clinical care of liver cirrhosis and improved surgical techniques have provided satisfactory outcomes in well-selected and optimised group of patients in procedures such as umbilical hernia repair [28] and laparoscopic cholecystectomy [29]. However, for colorectal pathologies that require major resection, a considerable peri-operative risk with a median overall complication rate of 47.1% still challenges the surgeon in offering the best treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Operative procedures in patients with liver cirrhosis are often associated with high incidence of morbidity due to bleeding risk from coagulopathy and complications associated with liver decompensation such as infective ascitic fluid, wound dehiscence/infection and multiorgan failure. Recent advances in the clinical care of liver cirrhosis and improved surgical techniques have provided satisfactory outcomes in well‐selected and optimised group of patients in procedures such as umbilical hernia repair [28] and laparoscopic cholecystectomy [29]. However, for colorectal pathologies that require major resection, a considerable peri‐operative risk with a median overall complication rate of 47.1% still challenges the surgeon in offering the best treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies found that emergent repair of hernia is associated with increased morbidity, mortality, and HLOS [ 3 , 12 , 16 , 29 , 30 , 31 ]. This highlights the need for early intervention and surveillance to prevent such complications requiring emergency surgery [ 26 , 32 ].…”
Section: Discussionmentioning
confidence: 99%